Transparent and Accountable Platforms with Open APIs - Bastos, Marco. T. (Statistical and Social Inquiry Society of Ireland, 2025)
This article examines the data access policies implemented by Twitter that transformed the platform into an open resource for academic research. We revisit the many Application Programming Interfaces that Twitter offered to developers and researchers and their role in building trust with social media companies. This includes REST, Search, Streaming, Academic, and Compliance APIs in addition to databases curated by the company and shared with the research community before its contentious acquisition by Elon Musk in late 2022 and its ensuing rebranding as X in July 2023. We conclude by outlining the requirements for transparent and accountable social media platforms and discussing the opportunities afforded by the EU’s Digital Services Act to advance this agenda.
read before the Society, 30th April 2025 - Symposium: Big Tech and Big Data - New Frontiers in Regulation
Keywords: open APIs; Twitter; DSA; content moderation; systemic risks; 314.15